Reliability of Jacket-Type Structure Considering the Reserve Strength Ratio (RSR) - Tito, Brigitta Violyna El; Prastianto, Rudi Walujo; Rosyid, Daniel Mohammad (International Journal of Marine Engineering Innovation and Research, 2024)
According to the International Energy Agency (IEA), the projected global energy demand will continue to increase by 45% by 2030, with an average growth rate of about 1.6% per year. Oil and gas are estimated to fulfil about 80% of the world's energy needs. One facility that supports oil and gas exploitation is an offshore structure of the jacket-type platform. The challenge in building a jacket platform is the cost and reliability of the structure. Costs must be kept to a minimum to maintain stable production prices. Offshore structures are designed to withstand extreme wave loads that can cause the collapse of individual components or the entire structure. So, it is necessary to analyze the ultimate strength of the jacket structure. Therefore, the author will conduct an ultimate strength analysis using the Non-Linear Pushover Analysis method to obtain the Reserve Strength Ratio (RSR). After that, a reliability analysis is carried out to determine the reliability of the structure under ultimate conditions using the Monte Carlo Simulation (MCS) method. The pushover analysis results in an RSR on the structure of 9.33. The results of the analysis of the reliability of the structure are 0.99997